1996
DOI: 10.1039/p29960001837
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and applications of azo-containing photodestructible surfactants

Abstract: Photodestructible surfactants, sodium 4-(2-cyano-2-undecylazo)benzoate and a series of sodium 4alkylphenylazosulfonates, have been synthesized and were shown to be surface active in solution, each exhibiting a distinct critical micelle concentration (CMC). UV irradiation of aqueous solutions of the alkylazobenzoate led to a distinct increase in surface tension, but even after complete photolysis significant surface activity remained, indicating a substantial amount of cage recombination after nitrogen evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…Among them, phenylazosulfonate, as shown in Figure 3, is a very interesting photosensitive group that can be changed from a negatively charged sulfonate to a positively charged diazo, and then to a neutral phenol derivative, by UV-light irradiation. [33,34] This great polarity variation has provided the surfactant with abundant applications in materials science, such as controllable surface tension and photocontrollable emulsifiers in emulsion polymerization, [35] photosensitive gelatin, [36] and photoinduced phase separation. [37] A similar concept can be extended to prepare photoresponsive amphiphilic polymers.…”
Section: Photoirradiated Irreversible Methodsmentioning
confidence: 99%
“…Among them, phenylazosulfonate, as shown in Figure 3, is a very interesting photosensitive group that can be changed from a negatively charged sulfonate to a positively charged diazo, and then to a neutral phenol derivative, by UV-light irradiation. [33,34] This great polarity variation has provided the surfactant with abundant applications in materials science, such as controllable surface tension and photocontrollable emulsifiers in emulsion polymerization, [35] photosensitive gelatin, [36] and photoinduced phase separation. [37] A similar concept can be extended to prepare photoresponsive amphiphilic polymers.…”
Section: Photoirradiated Irreversible Methodsmentioning
confidence: 99%
“…This lowenergy radiation should be harmless to proteins. Another approach has been to insert the light-sensitive diazosulfonate group between the polar head group and the tail of an anionic surfactant (55)(56)(57). As can be seen from Scheme 17, these surfactants are also similar in structure to the commonly used ABS.…”
Section: Uv-labile Surfactantsmentioning
confidence: 96%
“…Extensive studies involving an anionic photolyzable surfactant, sodium 4-hexylphenylazosulfonate (C 6 PAS), showed that UV light can provoke the breakdown of microemulsions formulated from mixtures with inert Aerosol-OT [19,20]. Photolysis of C 6 PAS switches the hydrophilic surfactant into insoluble hydrophobic components [19][20][21][22][23][24][25][26][27][28]. As outlined in Supporting material, there are two dominant photoproducts: the nonsurface active hexylbenzene and the weakly surface-active 4-hexylphenol.…”
Section: Introductionmentioning
confidence: 99%